Sigmund Freud's Psychoanalysis of the Main Character in the Short Story About the Name Majid Pucuk Works by Agus Khaidir - Ririn Herni Widiarini; Sri Suciati; Nazla Umaya Maharani (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Short stories often present an in-depth portrait of life through the thoughts, feelings, and behavior of the characters. The short story Ihwal Nama Majid Pucuk presents a story related to the psychological problems of its characters. The main character of the short story experiences both physical and mental conflicts. This study aims to reveal the psychology of the characters in the short story Ihwal Nama Majid Pucuk by Agus Khaidir which is analyzed from the aspects of id, ego, and superego. This study uses a qualitative approach with a descriptive analysis method with a literary psychology approach of Sigmund Freud's theory. The data for this study are in the form of quotations of sentences that represent the psychology of the short story characters. Data were collected through reading and note-taking techniques. Data analysis was carried out by recording/recording data and the analysis process. The results of the study show that elements of id, ego, and superego exist in the short story Ihwal Nama Majid Pucuk by Agus Khaidir. The character Abdul Majid shows a strong balance between emotional drives (id), self-control processes (ego), and moral values he holds (superego). Abdul Majid's id aspect appears in the form of the urge to satisfy feelings of anger, revenge, maintain self-esteem, and the desire to avenge his suffering. The ego aspect is evident through his ability to control his actions, adapt to his social environment, and display rational reactions to various pressures and conflicts. The superego, meanwhile, encourages Abdul Majid to demand a just and moral resolution, rather than resorting to violence. This research is expected to increase readers' interest and motivation in understanding the psychology of characters in literary works, allowing them to learn lessons for real life.